Integration of Demonstrative Teaching and Supporting Theories of Fluid Mechanics: A Literature Review - Arellano, Iranne Jay; Barrientos, Jorwin Ace; Castañeda, Mhea Lendie; Lozada, Jaren Paul; Mercado, Justine (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This review will give emphasis to the concept of demonstrative teaching to better improve the learning process of students in fluid mechanics. This paper is going to tackle the possible techniques students do to gain a better understanding of the concepts of fluid mechanics. With that, this review will also look at the impact of learning towards the students based on the number of demonstrations that they are making. This is where we will find out if there is a significant difference in the results with respect to the number of demonstrations performed. This paper will also discuss the most appropriate approach a beginner may take in handling a fluid mechanics class.